Analisis Paradigma Mimpi dalam Sudut Pandang Islam - sita isna malyuna (Nizham Jurnal Studi Keislaman, 2023)
Abstract Dreams are mental phenomena that occur during sleep. Precognitive dreams are a type of dream, where these dreams come true in the future. This dream is often experienced by certain people such as prophets, saints and others. The purpose of this article will be to discuss how dreams are from an Islamic point of view. The method in this article is library research. The results of the study show: First, the presence or absence of God's contribution that causes the sacredness of dreams. Second, the comparison of seeing images that appear when dreaming. Third, the difference in terms of dream axiology. Fourth, the ethics of interpretation or interpretation of dreams. All humans experience dreams that are synonymous with sleeping flowers or in the form of images that don't make sense, but dreams actually show the quality of one's spirit or soul. The better and clearer a person's soul is, the more meaningful the truth of his dreams will be. Therefore, it is desirable for humans and Muslims in particular, to always improve themselves both in external and spiritual practices, so that they are able to get dreams that are of good quality and contain truth. Keywords: Analysis, Paradigm, Dreams, Islam